PEMBERDAYAAN KADER TENTANG PERAWATAN BAYI BARU LAHIR DENGAN MENGOPTIMALKAN PELAYANAN KOMPLEMENTER - kurniyati, kurniyati; Febrina, Lydia; Puspita, Yenni (LPPM Universitas Al Muslim, 2024)
Newborn babies, especially those less than one month old, are the age group at highest risk of health problems, so they need appropriate supervision and treatment. Cadres play a role as community mobilizers, counseling and monitoring, who directly deal with social problems, including health problems faced by the community, so they play a big role in supporting the success of treatment of the newborns. This community service activity aimed to train the skills of posyandu cadres through empowering the role of posyandu cadres regarding care of newborn babies by optimizing complementary services in Kampung Delima Village, Rejang Lebong Regency. This activity was carried out from July to November 2023 targeting health cadres in Kampung Delima Village, East Curup District. Rejang Lebong Regency. Activities were carried out through training and mentoring of cadres. The results of this activities after training showed an increase in cadres' knowledge and skills regarding newborn care by optimizing complementary services, which include bathing babies and umbilical cord care using topical breast milk, correct breastfeeding techniques and baby massage in Kampung Delima Village.